The growth performances and the gut health parameters of Sentul chickens supplemented with various dosage of turmeric powder - INDRAWATI Y. ASMARA; TUTI WIDJASTUTI; IWAN SETIAWAN; ABUN ABUN; RUHYAT PARTASASMITA (Smujo International, 2018)
Asmara IY, Widjastuti T, Setiawan I, Abun, Partasasmita P. 2018. The growth performances and the gut health parameters of Sentul chickens supplemented with various dosage of turmeric powder. Nusantara Bioscience 10: 121-125. The aim of this study was to investigate the effect of different levels of turmeric powder (0, 1, 2, 3 g/kg) on production performance and the number of Escherichia coli and Staphylococcus aureus bacteria in the intestine of Sentul chickens. The results showed that addition of 3 g/kg of turmeric powder to diet significantly reduced feed intake (FI) and improved feed conversion ratio (FCR) of Sentul Chickens aged 9-16 weeks. The birds fed with control diet had the highest number of S. aureus and E. coli, while the birds fed with the diets added with 2 and 3 g/kg turmeric powder had the lowest number of bacteria. The study reveals that increasing levels of turmeric powder in diets had positive effects on bird’s performance and the number of intestinal bacteria. It can be concluded that a level of 3 g/kg turmeric powder in diets gave the best result due to significantly improved FCR.